2000
DOI: 10.1063/1.373830
|View full text |Cite
|
Sign up to set email alerts
|

Interface stress in Au/Ni multilayers

Abstract: Interdependence of elastic strain and segregation in metallic multilayers: An x-ray diffraction study of (111) Au/Ni multilayers J.The effect of intermixing on the apparent interface stress is studied in ͗111͘-textured dc-magnetron sputtered Au/Ni multilayers by use of two methods commonly used for determining interface stress. The method using profilometry and in-plane x-ray diffraction does not take intermixing into account and yields an apparent interface stress of Ϫ8.46Ϯ0.99 J m Ϫ2 . However, observed disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These values are much different from the d (111) values of 2.09 Å and 2.06 Å obtained for Ni multilayers grown with different metals such as Au and Co layers, respectively. 51,52 Since the thickness-dependent d (111) values of Ni/rubrene/Si are similar to those of Ni/Si, we used a common approach to estimate the lattice strain ( ε ) in our samples with the relation ε = ( a − a 0 )/ a 0 , where a 0 is the lattice constant of the bulk material and a is the lattice constant calculated from the XRD patterns through . 53–55 The lattice strain ε of the Ni layer experiences a tensile strain of magnitude for 0.96% and compressive strain of 0.31% for Ni(8)/rubrene/Si and Ni(8)/Si, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are much different from the d (111) values of 2.09 Å and 2.06 Å obtained for Ni multilayers grown with different metals such as Au and Co layers, respectively. 51,52 Since the thickness-dependent d (111) values of Ni/rubrene/Si are similar to those of Ni/Si, we used a common approach to estimate the lattice strain ( ε ) in our samples with the relation ε = ( a − a 0 )/ a 0 , where a 0 is the lattice constant of the bulk material and a is the lattice constant calculated from the XRD patterns through . 53–55 The lattice strain ε of the Ni layer experiences a tensile strain of magnitude for 0.96% and compressive strain of 0.31% for Ni(8)/rubrene/Si and Ni(8)/Si, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…40,50 This suggests that lattice strain of the Ni layer is different for thinner films on a buffered organic layer and a bare Si substrate. 51,52 Since the thicknessdependent d (111) values of Ni/rubrene/Si are similar to those of Ni/Si, we used a common approach to estimate the lattice strain (e) in our samples with the relation e = (a À a 0 )/a 0 , where a 0 is the lattice constant of the bulk material and a is the lattice constant calculated from the XRD patterns through…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…Spaepen also proposed a method to evaluate the interfacial stress by the curvature method, and showed that the interfacial stress can be tensile or compressive. A number of studies have also used similar methods for the evaluation of interfacial force in multilayer films [ 17 , 18 , 19 ]. However, this method evaluates the average interfacial force of two materials.…”
Section: Methodsmentioning
confidence: 99%